Brain magnetic resonance imaging fndings among children with epilepsy in two urban hospital settings, Kampala-Uganda: a descriptive study - Apolot, Denise; Erem, Geofrey; Nassanga, Rita; Kiggundu, Daniel; Tumusiime, Crescent Max; Teu, Anneth; Mugisha, Alex Mwesigwa; Sebunya, Robert (BMC Medical Imaging, 2022)
Epilepsy is one of the most common neurological conditions in children worldwide. Its presentation is heterogeneous, with diverse underlying aetiology, clinical presentation, and prognosis. Structural brain abnormalities are among the recognized causes of epilepsy. Brain Magnetic Resonance Imaging (MRI) is the imaging modality of choice for epilepsy workup. We aimed to determine the prevalence and describe the structural abnormalities identified in the brain MRI studies performed on children with epilepsy from two urban hospitals in Kampala, Uganda.
Keywords: Congenital; Epilepsy; Magnetic resonance imaging; Structural abnormality